MEKANISME PENERAPAN PP NO. 46 TAHUN 2013 PADA USAHA MIKRO KECIL DAN MENENGAH (Studi Kasus pada UD X, Ngawi, Jawa Timur Tahun 2014 – 2016) - Djoko Kristianto, Anisa Latifa, Fadjar Harimurti & (Universitas Slamet Riyadi, 2018)
The purpose of research is to analyze the mechanism of government regulation number 46 that is UD X, Ngawi, East Java in 2014 - 2016. This research is the case study in UD X. This research took primary data and secondary data obtained from UD X. Technical analysis of the data used is statistical analysis with Guttman scale, analysis of tax cutting, deposit and reporting. The result of statistical analysis with Guttman scale resulted a percentage of 47%, indicating that UD X less understood with the mechanism of applying PP No. 46. The analysis of tax deductions made by UD X in accordance with the laws and regulations, is evidenced by a monthly turnover deduction. The analysis of tax deposit made by UD X in accordance with the legislation, this is evidenced by the orderly make deposits every month at the post office or bank perception. Tax reporting analysis conducted by UD X in accordance with the laws and regulations, as evidenced by reporting the letter of tax payments of the year and the letter of annual tax payment in KPP Pratama Ngawi.Keywords: Income tax, micro small medium enterprises, government regulation number 46 of 2013.